Tinjauan Hukum Islam Terhadap Praktek Jual Beli Sistem Hutang Hasil Pertanian - Ngasifudin, Muhammad; Almunawaroh, Tri (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2021)
This reserch aims to analyze agricultural trading on credit system in islamic approach. This research was conducted in the village of Pahonjean. Majenang towards the welfare of farmers. Data collection was carried out by observation, and interviews. By using a qualitative approach the results showed that this system of accounts receivable has become a habit among farmers and the impression from this system is that new farmers can only fulfill their primary and secondary needs.